THE IRONY AND IRONIC IN THE LITERATURE AS SIGNS OF CONTEMPORARY CRITICAL REFLECTION - Stetsyuk, S. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article examines the role of irony and manifestation of ironic in the literature as the signs of critical reflection that arise in the process of human development and understanding of their being.